Transnational Capitalism and the Struggle over European. - Van Apeldoorn, Bastiaan (Routledge/RIPE series in global political economy., 2002)
This book presents an analysis of the transnational social forces in the making of a new European socio-economic order that emerged out of the European integration process during the 1980s and 1990s.